Volume 8: Turbomachinery, Parts A, B, and C 2012
DOI: 10.1115/gt2012-69554
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Discrete Tip Injection in a Two-Dimensional Streamline Curvature Method

Abstract: Fluid injection at the tip of highly loaded compressor rotors is known to be effective in suppressing the onset of rotating stall and eventually compressor instability. However, using such stability enhancement methods in a multistage compressor might not only stabilize certain stages but has also an impact on radial and axial matching. In order to account for tip injection during the early stages of compressor design, this paper focuses on the development of a method to model the physical effects underlying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The development of CSL for transonic flow velocities (high subsonic and low supersonic) is reported in [5]. The application of CSL in combination with a dif-fuser criterion enables the estimation of a resistance limit for a multi-stage axial compressor [6]; it also makes it possible to explore the effect of water injection [7] to the flow-through part of compressor.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The development of CSL for transonic flow velocities (high subsonic and low supersonic) is reported in [5]. The application of CSL in combination with a dif-fuser criterion enables the estimation of a resistance limit for a multi-stage axial compressor [6]; it also makes it possible to explore the effect of water injection [7] to the flow-through part of compressor.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The unsteady effect was used to capture the influence of tip injection with a streamline curvature method. 21 Zhou et al 22 found an optimal injection frequency to maximize the rotor stability enhancement. Hiller et al 23 stated that the effect of controlled pulsed injection was more pronounced than that of steady injection.…”
Section: Introductionmentioning
confidence: 99%
“…The stabilizing effect of tip injection can be briefly summarized as the unloading effect, [7][8][9][10][11] the action on TLF or endwall blockage, [12][13][14][15][16][17] and the unsteady effect. [20][21][22][23][24] However, it is difficult to evaluate the influence on compressor efficiency accurately for the tip injection with external air source. The injected air in RCTs is supplied with the compressed air in the compression system, which makes it easier to calculate the influence on the compressor efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…6 An optimized geometric shape for rectangular injector was achieved with fixed injection mass flow in Cassina et al 8 Weigl et al 12 and Dobrzynski et al 13 reported that the decrement of injection circumferential coverage to half or even less by reducing injector numbers made no obvious difference in stability improvement. However, Matzgeller et al 14 elaborated the importance of the unsteady effects of tip injection depending on injector numbers and successfully added the unsteady effects into their model. To the knowledge of the authors, the width of injector has not been treated as an independent geometric character and the corresponding influence has not been revealed.…”
Section: Introductionmentioning
confidence: 99%